Adaptação de metodologias de manejo reprodutivo como subsídios para a implantação de um programa de melhoramento genético da tilápia do nilo (oreochromis niloticus) variedade chitralada no centro de pesquisa em aquicultura-cpa/dnocs - Teixeira, Erivânia Gomes (2007)
The Nile tilapia Oreochromis niloticus is the most cultured species from the Cichlidae family. Despite its natural occurrence in Africa, it has been introduced in many countries including Brasil. The lack of management strategies for keeping the genetic variability of broodstocks produced a gradual loss of traits of aquacultural interest, and has created an urgent demand for genetic improvement of the cultured stocks. The purpose of the present work was to test and adapt a set of methods for the reproductive management of Nile tilapia variety chitralada, as a means for the future implantation of a program for genetic improvement of this species in the Center of Aquaculture Research (CPA/DNOCS) in Pentecostes, Ceará, Brazil. Protocols tested included anesthesia using Eugenol, individual tagging, sex differentiation, and collection of both morphometric (body weight, length and height) and meristic (number of eggs; characterization, motility, and criopreservation of the sperm) data. In addition, a protocol for DNA extraction using CTAB reagent was tested with good results. One experiment of reproduction efficiency was carried out in cages enclosed in hapas, and the proportion of broodstocks used was one male to each two female. The overall results provided some meaningful pieces of information that will assist the implantation of a program of genetic improvement for tilapia at the CPA/DNOCS.